STRATEGI PENGEMBANGAN WAKAF PRODUKTIF DALAM MENUMBUHKAN EKONOMI MASYARAKAT DI KOTA CILEGON BANTEN - Hendra Kholid; M. Dawud Arif Khan; M. Aqlus Salim (Jurnal Ekonomi dan Bisnis, 2023)
The results of this study indicate: First, mechanism waqf in implementing the Law no. 41 of 2004 as stipulated in article 43 paragraph 1 until 3, the concept of developing and managing waqf property is to be suitable principle sharia, to be developed and managed productively under its objectives, functions, and designations, and required guarantor. Second, Cilegon City applies its productive waqf management by renting out land, shophouses, photocopy machines, kiosks, boarding houses, and more. The reason is that the waqf assets owned by Cilegon City are mostly land and buildings. Third, a productive waqf has not brought any significant impacts on growing the community's economy in Cilegon City yet. because the bureaucracy or its management is not perfect and the waqf that is produced is not comprehensive. From previous research, the author agrees with what Annisa Fitria Utami et al. said in their scientific work entitled "Productive Waqf Management Strategy for the Welfare of the People" that the problem is in the naẓir. It is the incompetencies of the naẓir in managing waqf and the insufficient government funds allocation for waqf. In addition, the low literacy of the community and wāqif is also a problem. Therefore, the author suggests that the government should be more active in advancing waqf in Cilegon City to create rapid community economic growth. Thus, to discover further about the development of waqf in growing the community's economy in Cilegon, the author collects the data and information from various sources. The primary source is an interview with the Cilegon City BWI, District Religious Affairs Office, naẓir, and the waqf beneficiaries. Then the secondary source is by collecting relevant literature. The research type used here is field research with a qualitative descriptive analysis approach that describes data and information based on facts discovered in the field regarding the development of productive waqf in growing the community's economy in Cilegon City.